A Dual Volatility Conditioning with Moderation in the Hedge Fund Return Process - Joung Keun Cho (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One-month prior role of mediation by market momentum on the effect of market excess return to its contemporaneous hedge fund performance through the one-month prior level of VIX as the primary moderator is moderated if the indirect effect of the one-month prior market momentum depends on the return magnitudes of one-month prior VIX as the secondary moderator. This paper adopts quantitative approaches with behavioral implications to financial time-series applying the multiple moderator-conditional process models. Consistent with our view that hedge fund managers exhibit different skill sets in translating the implied volatilities especially in the equity market, we document some heterogeneity of processing momentum implications by dynamically adjusting risk-in/off behavior across hedge fund strategies. We subsequently show the test methodology when the indirect effect on the returns of various hedge fund strategies by market risk premium is moderated by any factor whenever two different moderators are switching their primary and the secondary roles of dependency.